Synthesis and Cytotoxic Activity against K562 and MCF7 Cell Lines of Some N-(5-Arylidene-4-oxo-2-thioxothiazolidin-3-yl)-2-((4-oxo-3-phenyl-3,4-dihydroquinazoline-2-yl)thio)acetamide Compounds - Cong T. Nguyen; Quang T. Nguyen; Phuc H. Dao; Thuan L. Nguyen; Phuong T. Nguyen; Hung H. Nguyen (Journal of Chemistry, 2019)
Ethyl 2-((4-oxo-3-phenyl-3,4-dihydroquinazolin-2-yl)thio)acetate (3) which was synthesized starting from anthranilic acid (1) via 2-thioxo-3-phenylquinazolin-4(3H)-one (2) reacted with hydrazine hydrate to afford 2-((4-oxo-3-phenyl-3,4-dihydroquinazolin-2-yl)thio)acetohydrazide (4). Reaction of (4) with thiocarbonyl-bis-thioglycolic acid gave a new compound name N-(4-oxo-2-thioxothiazolidin-3-yl)-2-((4-oxo-3-phenyl-3,4-dihydroquinazolin-2-yl)thio)acetamide (5). Knoevenagel condensation of (5) with appropriate aldehydes gave fourteen (Z)-N-(5-arylidene-4-oxo-2-thioxothiazolidin-3-yl)-2-((4-oxo-3-phenyl-3,4-dihydroquinazolin-2-yl)thio)acetamide compounds (6a–o) with moderate yield. The chemical structure of the compounds was elucidated on the basis of IR, 1H-NMR, 13C-NMR, and HR-MS spectral data. The 5-arylidene-2-thioxothiazolidinone compounds exhibited mild-to-moderate cytotoxic activity against both K562 (chronic myelogenous leukemia) cells and MCF7 (breast cancer) cells.